Critical appraisal of epidemiological studies and clinical trials - Elwood, J. Mark. (Oxford : Oxford University Press, 2007)
Critical appraisal is now accepted as central to the development of rational health care and evidence-based medicine, by applying it to questions of aetiology, clinical therapy, and health care management. The reader will learn how to assess the strengths and weaknesses of new studies, and how to conduct their own studies.
Previous ed.: 1998.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Epidemiology; Epidemiology -- Research; Clinical trials -- Evaluation